Extracellular matrix proteins and integrin receptors in reactive and non-reactive lymph nodes. - Castaños-Velez, E (1995)
The extracellular matrix (ECM) proteins collagen I, III and IV, laminin, fibronectin, vitronectin, thrombospondin, tenascin and their integrin receptors of the beta 1 and beta 3 subfamilies showed characteristic patterns of distribution in different compartments of non-reactive and reactive lymph nodes (human and monkey). This was particularly evident during development of germinal centres. Thus, ECM proteins (collagens, laminin, fibronectin and tenascin) were abundant in the interfollicular (T-cell rich) compartments of non-reactive as well as reactive lymph nodes. In primary follicles, collagen I, III and fibronectin were expressed but displaced by the expanding germinal centre during the formation of secondary follicles in reactive lymphoid tissues. The integrin subunits were mainly associated with endothelial cells and lymphoid cells in interfollicular areas, but were absent or only poorly expressed in primary as well as secondary follicles. Evidently the expression of ECM components and their integrin receptors is markedly down-regulated in the reactive, highly proliferative germinal centres.